Structure of riparian vegetation in Bongkasa Pertiwi Village, Abiansemal District, Badung Regency – Bali - Wijaya, I Made Saka; Yuni, Luh Putu Eswaryanti Kusuma; Sari, Ida Ayu Eka Pertiwi (Jurnal Biologi Udayana; Vol 25 No 2 (2021): JURNAL BIOLOGI UDAYANA, 2021)
Ayung river is the longest river in Bali. The middle part of the river is frequently utilized as rafting for tourism, such as in Bongkasa Pertiwi Village, Abiansemal District, Badung Regency – Bali. To preserve the river’s ecological function, the information of riparian vegetation as the dynamic component in river is highly required. This research aimed to study the structure of riparian vegetation in Bongkasa Pertiwi Village. The plot method was used and the study site was divided into three stations. Each station was composed by three replications with four plot variations: trees (20 x 20 m), poles (10 x 10 m), saplings (5 x 5), and herbs-shrubs (2 x 2 m). The data was analysed using vegetation analysis that completed with Importance Value (IV), Shannon-Wiener Diversity Index (H’), Index of Dominancy (C), and Index of Evenness (E). This study found that the structure of riparian vegetation in Bongkasa Pertiwi Village was in good condition which was indicated by the high abundance of local tree species. The floristic composition of riparian vegetation comprised by 18 species of trees, 18 species of poles, 21 species of saplings, and 29 species of herbs and shrubs. Cocos nucifera , Pterospermum javanicum , Bischofia javanica , Cananga odorata , Elaeocarpus serratus , Artocarpus heterophyllus , Coffea canephora , and Nephelium lappaceum were the species with the highest Importance Value (IV). The floor vegetation in form of herbs and shrubs was dominated by Sphaegneticola trilobata , Oplismenus burmanni , and Diplazium esculentum . Based on the Diversity Index (H’), Index of Dominancy (C), and Index of Evenness (E), diversity of riparian vegetation in Bongkasa Pertiwi Village was classified as medium category, without any dominated species, and the vegetation composition was equivalent.